2021
DOI: 10.1093/jscr/rjab398
|View full text |Cite
|
Sign up to set email alerts
|

Giant primary scrotal lipoma in a low-resource setting: challenges with diagnosis and review of literature

Abstract: Lipoma is the commonest benign mesenchymal tumor composed of matured adipocytes. A literature search revealed few reported cases of giant scrotal lipoma. This article aims to report a giant scrotal lipoma weighing 1100 g and illustrate our challenges with the diagnostic process in a low-resource setting. A 28-year-old male presented with a huge right scrotal mass. Examination revealed the mass had no cough impulse. It was firm, non-tender and lobulated, with definite edges. Scrotal sonography was suspicious of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Large scrotal lipomas often present with scrotal enlargement and discomfort[ 10 - 12 ]. A large right scrotal mass that weighed 1100 g was reported[ 5 ]. Yamamichi et al [ 13 ] reported a case of scrotal lipoma with a maximum diameter of 14 cm combined with liposarcoma (weight 250 g).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large scrotal lipomas often present with scrotal enlargement and discomfort[ 10 - 12 ]. A large right scrotal mass that weighed 1100 g was reported[ 5 ]. Yamamichi et al [ 13 ] reported a case of scrotal lipoma with a maximum diameter of 14 cm combined with liposarcoma (weight 250 g).…”
Section: Discussionmentioning
confidence: 99%
“…However, no pure lipoma was observed[ 1 ]. A study published in 1930 reported a giant scrotal lipoma weighing 480-1100 g[ 2 , 5 ]. Seidu et al [ 5 ] reported a large unilateral scrotal mass that weighed 1100 g in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…US is the primary modality for describing the abnormalities of the paratesticular space and it helps in the localization of the lesion and assessment of its consistency whether it is cystic or solid [8,9]. US is also the cheapest and readily available in lowresource settings, however, it is operator-dependent [10]. The US has low specificity in differentiating benign tumors from malignant and both of them present as non-specific painless paratesticular mass.…”
Section: Ali and Singhmentioning
confidence: 99%
“…Lesions with a complicated appearance are difficult to differentiate from the malignant counterpart of liposarcoma which accounts for 3-7% of all extra testicular tumors and surgery is often warranted [10]. Hence, with those diagnostic dilemmas and patients over concern about the mass, we proceeded with scrotal exploration and the complete excision of the mass.…”
Section: Ali and Singhmentioning
confidence: 99%